Perspektif Filosofis Sir Muhammad Iqbal Tentang Pendidikan Islam - Hidayatullah, Syarif (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
These are Sir Muhammad Iqbal’s philophical views and his thoughts on Islamic education.This is a qualitative descriptive study that describes Iqbal’s philophical views and his thought on Islamic education. This is a qualitative descriptive study that describes Iqbal’s philophical views and his thought on Islamic education. The study result is that the philophical views and his aim thought on Islamic education is how to create Insan Kamil. The Insan Kamil must be a basic goal of the aim education. According to Iqbal, there are main eight ideas to reconstruct the philosophically Islamic education by improving human dynamics and creativity. They are: the concept of individuality, the individual growth, the balance of spiritual and physical, uniting both individuality and society, an individual creativity, intelligence and intuition instruction, education of characters, and social education.